Urinary incontinence with special reference to the geriatric patient - M. Papadopoulos; R. Jordaan (South African Journal of Physiotherapy, 1999)
Problems involving the urinary tract, particularly urinary incontinence, tend to become more common with age. Urinary incontinence is a prevalent problem in the elderly and its medical, social and economic costs are significant. Patients are often too embarrassed or unwilling to seek treatment, as it is often seen as an inevitable corollary of old age, as it is not considered a life-threatening ailment and also because they assume that it is untreatable. The physiotherapist can play a very important role in both the prevention and management of incontinence, but sadly, very few physiotherapists are prepared to take this challenge. The aim of this review is to provide information, with specific reference to the elderly, regarding the prevalence, risk factors and causes of incontinence. The history and examining of the incontinent patient are discussed and management of the different types of incontinence are mentioned.